Limited correction of lumbar lordosis in the treatment of degenerative scoliosis. Issue 19 (May 2020) - Liang, Yan; Tang, Xiangyu; Zhao, Yongfei; Song, Kai; Mao, Keya; Liu, Haiying; Wang, Zheng
Abstract: Background: Patients suffering from degenerative scoliosis (DS) were commonly associated with coronal and sagittal imbalance which made deformity correction surgery necessary. The study aimed to explore the efficacy and feasibility of the limited correction of lumbar lordosis (LL) in the treatment of patients with DS. Methods: This was a retrospective study including 58 DS patients who underwent spinal deformity correction surgery and were followed up at least 2 years between January 2013 and January 2017. According to the difference of postoperative LL, the patients were divided into 2 groups: the limited correction group: Pelvic incidence(PI)–18°⩽ LL<PI–9° and the control group: PI–9°⩽ LL<PI+9°. There were 31 patients in the limited group, and 27 patients in the control group. The clinical and radiographic outcomes were compared preoperatively and at the last follow-up evaluation. Results: There was no significant difference between the 2 groups preoperatively ( P > .05). In terms of surgery, the limited group had less intra-operative blood loss and operation time ( P < .05). At the last follow-up, significant differences were found in terms of LL(−38.2 ± 4.7° and -46.9 ± 4.7°), PT (18.8 ± 5.2° and 11.1 ± 3.6°), sacrum slope (33.7 ± 7.0° and 41.4 ± 6.1°) ( P < .05), while there were no significant differences in terms of lumbar Cobb angle (10.5 ± 9.3°and 8.3 ± 6.7°), Oswestry Disability Index scores (25.6 ± 10.2 and 26.4 ± 12.1), and JOA scores (23.6 ± 5.2 and 22.3 ± 5.7) ( P > .05). Conclusion: Limited correction of LL in the treatment of DS patients can achieve favorable clinical outcomes including effective Cobb angle correction with less blood loss and operative time.